The non-sovereign territories: Economic and environmental challenges of sectoral and geographic over-specialisation in tourism and financial services. (July 2021) - Armstrong, Harvey W; Read, Robert
This paper analyses the economic and geographic characteristics of the world's principal non-sovereign territories in the context of the growth challenges facing small economies. These territories enjoy high degrees of policy autonomy within a complex array of relationships with their metropolitan countries. Seven of the ten metropolitan powers are European and account for 38 of the 49 inhabited non-sovereign territories. The territories' distinct economic and geographic characteristics, notably small size and remoteness, have led to their adopting similar niche sectoral growth strategies to those of small sovereign states and a reliance upon tourism and financial services. In spite of the growth challenges faced, most of these territories have attained high levels of per capita gross national income, placing them in the World Bank High Income category. Global heating, economic crises and regional environmental shocks, along with growing international protectionist sentiments, however, raise critical questions regarding the continued viability of their traditional growth strategies, particularly their heavy reliance upon environmentally harmful long-haul air travel and cruise tourism. This paper bridges the gap between large-scale growth studies, which generally overlook non-sovereign entities, and single case studies to examine the determinants of the growth success of non-sovereign territories and their future growth challenges given the pressing need for both economic and environmental sustainability.